The Effect of Inquiry-Based STEM Learning Strategy toward Students’ Writing Abilities at Eighth Grade of SMP Negeri 15 Bengkulu City - Erviona, Lussy; Maisarah, Ira; Sujarwati, Iis (Universitas PGRI Semarang, 2023)
The objective of this study was to reveal the effects of Inquiry-Based STEM Learning Strategy toward students’ writing ability at the eighth-grade students of SMP Negeri 15 Kota Bengkulu. Quasi-experimental design was implemented in this study. Eight grade students of SMP Negeri 15 Kota Bengkulu were participated in this study. The findings revealed a significant difference between the writing abilities of students taught using the Inquiry-Based STEM strategy and the writing abilities of students taught simply using scientific approach which is used as conventional techniques. It was found from the post-test results that there was significant effect toward students' writing ability after receiving six treatments. The results independent sample test revealed that the Inquiry-Based STEM technique had a significant impact toward students' writing abilities. The mean pre-test writing skill score for the control and experiment groups was found to be slightly comparable. However, the writing score of the experiment group was higher than the control group. Thus, it can be concluded that Inquiry-Based STEM strategy gives positive effect toward students’ writing ability and is proved to be effective strategy in teaching writing. Finally, it is suggested that teachers comprehend and apply the Inquiry-Based STEM strategy while teaching writing because it has been demonstrated that this technique may improve the teaching learning process. It is also suggested that additional studies perform study on the use of the Inquiry-Based STEM method in various grades or schools.